The Issue of Vision By Ahmed Al Manjour - Yahya Ben Abdelouahab (LECTURES: Journal of Islamic and Education Studies, 2024)
The Islamic methodological approach to thinking and deriving evidence through argumentation and logical principles has been highlighted. Muslims, especially Moroccans, haven't solely relied on traditional evidence to establish beliefs and respond to opponents. They have also bolstered their perspectives with rational evidence, excelling in this regard. Ahmed al-Manjour, through the manuscripts we studied in this paper, revealed the vast array of rational methods he employed to defend prevalent beliefs in Morocco. This includes the freedom of thought, creativity, and classification that prevailed during the Saadi dynasty in Morocco. For al-Manjour, the matter of "al-Nathar" (contemplation) is fundamentally based on the necessity of broad knowledge in various sciences and disciplines to arrive at the correct evidence. The process of thinking and deriving judgments only occurs after comprehending numerous mental and transmitted sciences. Thus, the contemplation of religious and worldly matters isn't arbitrary. By doing so, he excludes laypeople and those unfamiliar with many sciences from the circle of deducing beliefs and determining people's fates. He also refutes viewpoints that hinder Islamic heritage for any intellectual direction that relies on reason and logic in thinking and presenting arguments and evidence.